OUTCOME ANALYSIS OF TOTAL LARYNGOPHARYNGEAL OESOPHAGECTOMY IN CARCINOMA HYPO-PHARYNX AND CERVICAL ESOPHAGUS, WITH STOMACH RECONSTRUCTION - Majeed, Farhan Ahmad; Aslam, Sohail; Farooq, Shahid; Ali, Ahmad; Raza, Ahmed; Zafar, Usama (Journal of Ayub Medical College Abbottabad, 2020)
Background: Upper cervical oesophageal and hypo-pharyngeal malignancies pose significant challenges in surgical management. In advanced tumours total laryngopharyngeal esophagectomy (TLPO) and gastric pull up provides excellent result. Methods: It is a descriptive case series and was conducted from Jan 2010 to Jan 2017. 35 patients underwent TLPO. The inclusion criteria were; tumours of hypo-pharynx which allow tumour free resection margins and cervical oesophageal tumours not involving mediastinal trachea. There were no clinically palpable cervical lymph nodes. Patients with locoregional advanced disease and poor performance status were excluded. All cases underwent standard one stage TLPO with bilateral inter-jugular lymph nodal clearance. Minimal invasive techniques used in three cases. Results: Out of 35 patients, n=21 (60%) of patient had lesion of hypopharynx with post cricoid involvement, n=13 (37.1%) had primary tumour of cervical oesophagus abutting pharynx and cricoid and only one patient had a tumour of hypopharynx with perforation. Histopathological conformation of diagnosis done in all patients preoperatively which showed Well differentiated Squamous cell in n=19 (54.28%), moderately differentiated squamous cell in 28.57% (n=10). Post-operative staging of the patients 74.28% (n=26) fall in stage 3. Operative time was less than 3 hours in 17 patients with two team technique, between 3-4 hours in 8 patients and more than 4 hours in 3 patients. SVT in 14.28% (n=5), Atrial Fibrillation in 5.71% (n=2). Chest complications including pneumothorax in 11.43% (n=4), basal atelectasis in 22.86% (n=8), pulmonary embolism in 2.85% (n=1), aspiration in 8.57% (n=3) and tracheal stenosis in n=1, 5.71% (n=2) cases had anastomotic leak . Postop 28 days mortality was 8.57% (n=3). Conclusions: TLPO with stomach pull up offer good results in patients with resectable disease with acceptable morbidity and mortality in operable patients. Keywords: Carcinoma hypopharynx; Carcinoma oesophagus, Cervical oesophagus, Laryngopharyngeal esophagectomy